2011
DOI: 10.2138/am.2011.3786
|View full text |Cite
|
Sign up to set email alerts
|

A new type of high-pressure low-flow metering valve for continuous decompression: First experimental results on degassing of rhyodacitic melts

Abstract: A novel type of high-pressure low-flow metering valve has been designed for experiments at continuous decompression in internally heated pressure vessels (IHPV) at pressures up to 500 MPa and temperatures up to 1500 °C. It consists of a modified high-pressure valve coupled with a piezoelectric nanopositioning system. The piezoelectric actuator (1) positions the needle of the valve statically with very high precision on a nanometer scale for infinitesimally slow decompression and, alternatively, (2) opens and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…The IHPV is equipped with a special high-P valve construction (Nowak et al, 2011), facilitating both CD and SD. The super-liquidus starting conditions of 200 MPa and 1323 K as well as the range of nominal decompression rates from 0.0028 to 1.7 MPa·s − 1 were adopted from Iacono Marziano et al (2007).…”
Section: Decompression Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The IHPV is equipped with a special high-P valve construction (Nowak et al, 2011), facilitating both CD and SD. The super-liquidus starting conditions of 200 MPa and 1323 K as well as the range of nominal decompression rates from 0.0028 to 1.7 MPa·s − 1 were adopted from Iacono Marziano et al (2007).…”
Section: Decompression Experimentsmentioning
confidence: 99%
“…To date, only few decompression experiments were performed using CD with reasonable decompression rates (e.g., Mangan and Sisson, 2000;Brugger and Hammer, 2010;Pichavant et al, 2013). The SD technique was therefore compared to true, continuous decompression by Nowak et al (2011) to determine the influence of decompression path on melt degassing. A hydrous, rhyodacitic melt was decompressed at a nominal decompression rate of 0.28 MPa·s −1 with SSD, MSD and CD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples were all heated at a rate of 50°C/min and annealed for 20 h at 300 MPa, 1030°C and QFM + 2 in IHPV to ensure similar starting conditions prior to the decompression. Isothermal decompression was performed at 1030°C by releasing P continuously from 300 to 70 MPa by using an appropriate decompression valve (Nowak et al, 2011). The r was adjusted to 0.01, 0.1 or 1 MPa/s, and was constant for each experiment.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Recent studies have shown that decompression style (i.e., single-step vs. multi-step vs. continuous decompression) can affect bubble formation and, thus, most likely also DIC to a significant extent (Brugger and Hammer, 2010;Nowak et al, 2011;Fiege et al, 2014b). Thus, we performed continuous decompression experiments at rates of 0.01, 0.1 and 1 MPa/s.…”
Section: Introductionmentioning
confidence: 99%